(untitled) (Journal of Comparative & International Higher Education, 2022)
This article examines how the pedagogy of Global Positioning Leadership (GPL) enhanced the educational and global leadership mindset of graduate students who participated in three short-term study abroad programs of Cuba (2015), and Brazil (2016 and 2017). In this study, GPL also made use of grounded theory to analyze the change of worldview students experienced upon taking this interdisciplinary course. The focus was to assist students to achieve cross-cultural success, address serious issues in culturally relevant ways, and to gain a peak learning experience that can propel them toward relevant action. To assess students’ change of worldview, GPL proceeded through five stages: 1) fleshing out individual preconceptions; 2) writing up four individual goals; 3) analyzing conflicting narratives; 4) engaging in experiential learning; 5) mapping post-conceptions. Findings reveal that student immersion in Global South social realities results in significant individual, social, educational and professional change of worldviews.